Keanekaragam Piper spp (Piperaceae) di Hutan Taman Wisata Alam Situ Gunung Taman Nasional Gunung Gede Pangrango, Sukabumi - Inggit Puji Astuti; Esti Munawaroh (Journal of Tropical Ethnobiology, 2021)
The Situ Gunung Natural Park forest, Mount Gede Pangaro National Park, Sukabumi is located in Cisaat Village, Kadudampit District, Sukabumi, which is about 16 km from the city of Sukabumi. As a natural tourism area, the forest condition is still quite good with the vegetation that makes up the forest is dominated by Schima walichii, Altingia Excelsa and Castanopsis argantea. The plants that make up the forest floor are also quite varied, including those from the Araceae, Melatomataceae family and the Piperaceae family. From the results of the Piper diversity study, there were 8 types of pipers found, namely the Piper abbreviatum Opiz; Piper arcuatum Blume; Piper baccatum Blume; Piper betle L.; Piper flavomarginatum Blume; Piper lowong Blume ; Piper miniatum Bl. dan Piper sulcatum Blume. The discovery of P.flavomarginatum in this area had never been reported before and it was the second discovery after the discovery of this type in the protected forest of Mount Slamet, Central Java for the Java region. The types that had been used by the public were P.betle for traditional medicine and modern medicine which were processed as industrial products with sufficient economic value. Although the other seven types of piper that were discovered have not been utilized by the community, this germplasm is very important to be an educational material about natural wealth that needs to be explored for its potential.